The Role of the Glycocalyx in the Pathophysiology of Subarachnoid Hemorrhage-Induced Delayed Cerebral Ischemia - Schenck, Hanna; Netti, Eliisa; Teernstra, Onno; De Ridder, Inger; Dings, Jim; Niemelä, Mika; Temel, Yasin; Hoogland, Govert; Haeren, Roel (Frontiers in Cell and Developmental Biology, 2021)
The glycocalyx is an important constituent of blood vessels located between the bloodstream and the endothelium. It plays a pivotal role in intercellular interactions in neuroinflammation, reduction of vascular oxidative stress, and provides a barrier regulating vascular permeability. In the brain, the glycocalyx is closely related to functions of the blood-brain barrier and neurovascular unit, both responsible for adequate neurovascular responses to potential threats to cerebral homeostasis. An aneurysmal subarachnoid hemorrhage (aSAH) occurs following rupture of an intracranial aneurysm and leads to immediate brain damage (early brain injury). In some cases, this can result in secondary brain damage, also known as delayed cerebral ischemia (DCI). DCI is a life-threatening condition that affects up to 30% of all aSAH patients. As such, it is associated with substantial societal and healthcare-related costs. Causes of DCI are multifactorial and thought to involve neuroinflammation, oxidative stress, neuroinflammation, thrombosis and neurovascular uncoupling. To date, prediction of DCI is limited, and preventive and effective treatment strategies of DCI are scarce. There is increasing evidence that the glycocalyx is disrupted following an aSAH, and that glycocalyx disruption could precipitate or aggravate DCI. This review explores the potential role of the glycocalyx in the pathophysiological mechanisms contributing to DCI following aSAH. Understanding the role of the glycocalyx in DCI could advance the development of improved methods to predict DCI or identify patients at risk for DCI. This knowledge may also alter the methods and timing of preventive and treatment strategies of DCI. To this end, we review the potential and limitations of methods currently used to evaluate the glycocalyx, and strategies to restore or prevent glycocalyx shedding.